Identification of the consequences of battle operations and the occupation of state territories in accounting - O.S. Gorai (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The research deals with the process of identifying the consequences of battle operations and the occupation of state territories due to their influence on the separate objects of accounting. The overall structure of the consequences of emergencies in the context of the objects that make up and provide economic activity is presented. The place of the consequences of battle operations and the occupation of state territories in the system of accounting objects are determined. The article describes the consequences of battle operations and the occupation of state territories for different economic entities depending on their territorial location to emergency situations and their groups and properties are determined as the following: they are located on the territory of battle operations controlled / uncontrolled by the state authorities; they are on the occupied territories, a separated unit or a part of production facilities located on the territory of battle operations controlled / uncontrolled by the state authorities; a separated unit or a part of production facilities located on the occupied state territory collaborate / collaborated with the companies that are on the territory of fighting operations, which are uncontrolled by public authorities or on the state-occupied territory. The information model of interactions between economic entities as a result of battle operations and the occupation of state territories is developed.